Road Access Tracking Using GNSS Receiver at Taman Universiti, Parit Raja, Johor - Abdul Malek, Afif Rizqin; Suhandri, Hendy Fitrian (Recent Trends in Civil Engineering and Built Environment, 2021)
Global Navigation Satellite System (GNSS) plays a significant role in maximum precision in navigation, positioning, timing and scientific issues related to precise positioning. The GNSS observation including Precise Point Positioning (PPP) method that estimate the observation with errors as small as a few centimeter (up to 3 cm) and provide a high level of accuracy position from a single receiver. In addition, the current GNSS receiver in the engineering world will improve efficiency and provide better customer service. In contrast, the PPP also has disadvantage such as the amount of time required to resolve the cycle’s difficulty. The data were collected using the Leica Viva GS10/GS15 and processed using the Canadian Spatial Reference System Precise Point Positioning (CSRS-PPP), RTKLib and Translation, Editing and Quality Checking (TEQC) services. Moreover, the data was analyzed using Microsoft Excel tools. The file is format .m00 and must be output in observation (.21o) and navigation (.21n) RINEX file. The value of elevation cut-off in CSRS-PPP is 7.5° and the elevation mask in RTKLib software used is 15%. In addition, the value of fixed ambiguities from the results is 51.47%.